Blood-derived dendritic cell vaccinations induce immune responses that correlate with clinical outcome in patients with chemo-naive castration-resistant prostate cancer. Issue 1 (14th November 2019) - Westdorp, Harm; Creemers, Jeroen H. A.; van Oort, Inge M.; Schreibelt, Gerty; Gorris, Mark A. J.; Mehra, Niven; Simons, Michiel; de Goede, Anna L.; van Rossum, Michelle M.; Croockewit, Alexandra J.; Figdor, Carl G.; Witjes, J. Alfred; et al.
Abstract : Background: Clinical benefit of cellular immunotherapy has been shown in patients with castration-resistant prostate cancer (CRPC). We investigated the immunological response and clinical outcome of vaccination with blood-derived CD1c + myeloid dendritic cells (mDCs; cDC2) and plasmacytoid DCs (pDCs). Methods: In this randomized phase IIa trial, 21 chemo-naive CRPC patients received maximally 9 vaccinations with mature mDCs, pDCs or a combination of mDCs plus pDCs. DCs were stimulated with protamine/mRNA and loaded with tumor-associated antigens NY-ESO-1, MAGE-C2 and MUC1. Primary endpoint was the immunological response after DC vaccination, which was monitored in peripheral blood and in T cell cultures of biopsies of post-treatment delayed-type hypersensitivity-skin tests. Main secondary endpoints were safety, feasibility, radiological PFS (rPFS) and overall survival. Radiological responses were assessed by MRIs and contrast-enhanced 68 Ga-prostate-specific membrane antigen PET/CT, according to RECIST 1.1, PCWG2 criteria and immune-related response criteria. Results: Both tetramer/dextramer-positive (dm + ) and IFN-γ-producing (IFN-γ + ) antigen specific T cells were detected more frequently in skin biopsies of patients with radiological non-progressive disease (5/13 patients; 38%) compared to patients with progressive disease (0/8 patients; 0%). In these patients with vaccination enhanced dm + and IFN-γ + antigen-specific T cells median rPFS was 18.8 months ( n = 5) vs. 5.1 months ( n = 16) in patients without IFN-γ-producing antigen-specific T cells ( p = 0.02). The overall median rPFS was 9.5 months. All DC vaccines were well tolerated with grade 1–2 toxicity. Conclusions: Immunotherapy with blood-derived DC subsets was feasible and safe and induced functional antigen-specific T cells. The presence of functional antigen-specific T cells correlated with an improved clinical outcome. Trial registration: ClinicalTrials.gov identifier NCT02692976, registered 26 February 2016, retrospectively registered.